The Coastal Area Development Using GIS (Review of GIS Application Models) - Prastowo Sutanto (Forum Geografi, 1996)
GIS, Geographical Information System, is a means that an be used to plan and to develop the coastal area because in carrying out the analysis this system combines the space data and their  attributes. The activities done among others the prototype development of algae cultivation and tourism ativities, the development of fish pond location, the reclamation of the Jakarta Bay, and the concept of development the floating “Keramba” for pearl oysters and white sea fish similar to sole. GIS analysis with heaviness and overlay mapping yields the appropriate map to plan and to develop the coastal area. The result of GIS analysis can be used to plan and to develop the coastal area.